Cover Picture: DNA Triplexes That Bind Several Cofactor Molecules (Chem. Eur. J. 51/2015). Issue 51 (4th December 2015) - Vollmer, Sven; Richert, Clemens
Abstract : Synthetic DNA sequences can be used to store and release ATP via base pairing. The DNA binding motifs are reminiscent of a honey comb in that they contain cavities for storing energy‐rich biomolecules. For more details see the Full Paper by C. Richert and S. Vollmer onpage 18613 ff.